Early differential diagnosis of infantile neuronal ceroid lipofuscinosis, Rett syndrome, and Krabbe disease by CT and MR. - Vanhanen, S L; Raininko, R; Santavuori, P (American Journal of Neuroradiology, 1994)
PURPOSE To compare early radiologic findings in three clinically similar progressive encephalopathies of childhood. METHODS Brain CT and/or MR studies were done in 57 children 3 to 36 months of age: 16 with infantile neuronal ceroid lipofuscinosis, 5 with Rett syndrome, 6 with Krabbe disease, and 30 control subjects with normal neurologic status. In addition, previous descriptions in the literature were collected. RESULTS No significant changes were seen in Rett syndrome. Early atrophy was found in infantile neuronal ceroid lipofuscinosis and in Krabbe disease, being more severe in the latter. The thalami were hyperdense in 4 of 13 patients with infantile neuronal ceroid lipofuscinosis and in 1 of 4 patients with Krabbe disease (in the literature in 12 of 30 examinations). Cerebral calcifications and density abnormalities in the cerebral and cerebellar white matter were seen in Krabbe disease only. On MR, the white matter changes in the two diseases were differently located. In every patient with infantile neuronal ceroid lipofuscinosis, decreased T2 signal was seen in the thalami and periventricular high-signal rims after the age of 13 months. Hypointensity of the thalami and basal ganglia was seen in both diseases, but Krabbe disease showed more variations. Abnormalities of cerebellar intensity were found in Krabbe disease only. CONCLUSIONS CT and MR are of value in the differential diagnosis of these three diseases. MR especially facilitates the early diagnosis of infantile neuronal ceroid lipofuscinosis.